Expert System, Vertigo, Website PERANCANGAN SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT VERTIGO BERBASIS WEBSITE: PERANCANGAN SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT VERTIGO BERBASIS WEBSITE - Miharja, Satriya (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2021)
Vertigo is a symptom of disease, the cause can be from several diseases. Vertigo comes from the Greek "vetere" which means spinning or twisting. Vertigo can occur over a period of time, hours or even days. Patients usually feel themselves or the room around them as if spinning, dizzy, nauseated or walking becomes unstable. Patients at first did not know the types of symptoms or diseases they suffered because of the lack of information they knew. If the sufferer wants to know about the symptoms, causes and how to deal with it, they will go to the doctor for consultation. However, this cannot be done by everyone, perhaps because of insufficient economic factors or because of the demands of their busy schedules and activities so that they cannot adjust to the doctor's practice consultation schedule. One way to overcome this problem is that a health service is needed by creating an expert system to diagnose vertigo that can be enjoyed by sufferers effectively, efficiently and economically. Based on the results of trials on several respondents, namely: ordinary people can better understand the types of vertigo experienced and can be implemented to assist in the world of health in the health sector, can help users to understand information on types of vertigo in a shorter time and can relieve a person experts in detecting early symptoms of vertigo so that not all people have to visit a doctor if the vertigo they experience is just a normal symptom.